Raman spectroscopy of bottom-up synthesized graphene quantum dots: size and structure dependence. Issue 35 (28th August 2019) - Dervishi, Enkeleda; Ji, Zhiqiang; Htoon, Han; Sykora, Milan; Doorn, Stephen K.
Abstract : Dependence of Raman spectra on nanoparticle size was determined for a series of strongly confined graphene quantum dots. Abstract : Graphene quantum dots (GQDs) have attracted significant interest as synthetically tunable optoelectronic and photonic materials that can also serve as model systems for understanding size-dependent behaviors of related graphene structures such as nanoribbons. We present a Raman spectroscopy study of bottom-up synthesized GQDs with lateral dimensions between 0.97 to 1.62 nm, well-defined (armchair) edge type, and fully benzenoid structures. For a better understanding of observed size-dependent trends, the study is extended to larger graphene structures including nano-graphene platelets (>25 nm) and large-area graphene. Raman spectra of GQDs reveal the presence of D and G bands, as well as higher order modes (2D, D + G, and 2G). The D and G band frequencies and intensity were found to increase as GQD size increases, while higher order modes (2D, D + G, and 2G) also increased in intensity and became more well-defined. The integrated intensity ratios of D and G bands ( I D / I G ) increase as the size of the GQDs approaches 2 nm and rapidly decrease for larger graphene structures. We present a quantitative comparison of I D / I G ratios for the GQDs and for defects introduced into large area graphenes through ion bombardment, for which inter-defect distances are comparable to the sizes of GQDs studied here. Close agreement suggests the I D / I G ratio as a size diagnostic for other nanographenes. Finally, we show that Raman spectroscopy is also a good diagnostic tool for monitoring the formation of bottom-up synthesized GQDs.